PERAN GURU TAMAN PENDIDIKAN AL-QURAN SEBAGAI PEMBIMBING DALAM MEMBINA KARAKTER RELIGIUS ANAK DI MASJID JAMI’ATUL KHAIRIAH DESA SEKUDUK - Zulfadli Rizki; Arnadi, Susilawati (ADISAM PUBLISHER, 2025)
This thesis discusses the role of teachers at the Quran Education Park (TPA) as mentors in fostering children's religious character. The study has two main objectives: first, to describe the role of TPA teachers as mentors in shaping children's religious character at the TPA Jami’atul Kahairiah in Sekuduk Village. Second, to analyze the methods used by the teachers in developing children's religious character at the Jami’atul Khairiah Mosque in Sekuduk Village. This research employs a qualitative approach with a descriptive nature and is a field research study. The data collection techniques include three methods: observation, interviews, and documentation. The findings of this study are as follows: first, the role of TPA teachers as mentors in shaping children's religious character at TPA Jami’atul Kahairiah in Sekuduk Village includes being a guide in learning, a mentor in social development, and a counselor in personal issues. Second, the methods used by teachers to foster children's religious character at the Jami’atul Khairiah Mosque in Sekuduk Village are: the dialogue method, the habituation method, the advice method (mau’izah), and the role-model method